Martha Culler Plyler - (:unkn) unknown (Wake Forest University)
Info from OH# 1099/transcripts 1 & 2
Martha Culler Plyler was asked to come to Bowman Gray School of Medicine in 1972 to run the Multilith printing press that apparently no one else knew how to run. While running the press in the Purchasing Department, she also learned about that department. In 1975, she became a Purchasing Agent Manager. She retired in 2004 after serving over 30 years at the Medical Center.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth